Romania: State Aid Law in Romania - Veress, Emőd (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter examines the state aid law in Romania, focusing on its legal framework, key provisions, and recent developments. It provides an overview of the regulatory framework governing state aid in Romania, including the relevant legislation, regulations, and guidelines. Apart from analysing the criteria and procedures for granting state aid, it also discusses the role of the Romanian competition authority in enforcing state aid rules. Examining recent case laws and decisions related to state aid in Romania, it highlights the legal realities of state aid. Overall, it offers insights into the state aid regime in Romania and its implications for businesses, government entities, and the broader economy.Keywords: State Aid Law, Romania, Legal Framework, Competition Authority, Government Entities